FOOD SECURITY POLICY ANALYSIS PERPECTIVE ON FOOD SELF-SUFFICIENCY VILLAGE PROGRAMME CASE IN CENTRAL JAVA INDONESIA - Muhamad Rusliyadi (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
This purpose of the research is analyses of the Food Security Policy In Indonesia Case Food Self-Sufficiency Village Programme (DMP Programme) in terms of the role, implementation and impact of the DMP Programme. This analysis method was used a policy strategy using SWOT analysis. The expected benefit of the analysis is to provide a description of the output national and grassroots levels. Furthermore, of analysis was used the Analytic Hierarchy Process (AHP) method. The result of the result is on the impact of the program on village level revealed that the total score of (S) - (W) factor value of 0.24 and the total score (O) - (T) factor is 0.17. These positive values mean that the impact of the program generally showed relative success in terms of making some improvements. However, because of the severe conditions of poor households, the impact of the Programme has not been significant enough in changing the wellbeing of the community. The conclusion of the research are first, pay more attention to ensure community involvement and active participation in the Programme: the focus should be on poor households, because most of these are not active in the village. Second, in the short term, the Programme has very significant impacts: it can contribute to increased income and food security of poor households but the villages have been running the Programme only for about four years and there is a need to ensure the sustainability of the Programme. Third, the sustainability of the Programme at village level is needed and more effort needs to be made for farmer groups not to become too dependent on fund assistance.